Dicamba volatility assessment in a tropical environment - Antuniassi, Ulisses R. [UNESP]; Carbonari, Caio A. [UNESP]; Mota, Alisson A. B.; Checheto, Rodolfo G.; Carvalho, Fernando K.; Lopez Ovejero, Ramiro F.; Palhano, Matheus G.; Barbosa, Henrique N.; Velini, Edivaldo D. [UNESP]; Pai, Naresh (Advances in Weed Science, 2024)
Background: The use of the herbicide dicamba has significantly increased in Brazilian agriculture, has potential for volatilization and risk of injury to sensitive agricultural crops and environmental contamination. Objective: The objective of this research was to evaluate the behavior of dicamba volatility under application conditions in commercial crops in tropical climate conditions in Brazil. Methods: Six field experiments were conducted from 2018 to 2020 in 3 different states of Brazil to provide a quantitative assessment of dicamba volatility. Aerodynamic and integrated horizontal flux methods were used to estimate the volatile flux and mass loss of dicamba within 72 hours after application. Results: The results showed that the flux of volatilized dicamba peaked in the first few hours after application, decreasing drastically approximately 20 hours after application. The cumulative mass loss of dicamba was 0.15±0.08% of the applied dose. The average in-field air concentration (38.66±9.52 ng m3) represented only 28% of the regulatory no observable adverse effect concentration (NOAEC) established by the USEPA. Conclusions: Based on these results, vapor drift related to dicamba volatility under application conditions in tropical regions in Brazil was similar to or lower than the results reported in the literature for temperate climate regions.
Keywords: Auxinic Herbicide; Off-Target Movement; Vapor Drift; Volatilizatio